SURVEI PRAKTEK AKREDITASI LEMBAGA PENDIDIKAN KEJURUAN DAN TEKNOLOGI(VIET) DI NEGARA ANGGOTA ASEAN
Syney prqctice of WET accreditation in SHMEO member Countries lnd threb major objectives. These objectives were: l) to prwide information -in ionnection with accreditation; 2) tofacilitate information base - WET instinition for developins other relevant research; j) to enhanbe the Center’s’program in frnduc_ ting ap4lild rgsegrch in WET areas. The’sttidy Used survey approach in whlch reiatgd data were gathered with research question as-gltide oJstudy. The questionnoive center and Jormal -all was developed-bi the docamentation was used to pather" iffirmation. Before contributed to the respondenYts, the guestion_ naire was validated b1 using content -vakdity. A ndeded From the survey praclice of WET Accreditation had frye findinps relate to institutional accreditation. These names of rutional accreditation body findings’incfuded: -sidy "firstlv. NABI were udioi-i’fro* country tg cogilry. There were two typei of stntctural’NAB orggruzafion. Ihe. Notiotlal accreditation body consisted poveril- ment olJicer only, and the national accr6ditation boZv kat ?g iy:d !l- g:!,1yment oficers, pnvate.persons, and coimunity leaders- Jecofidty, the national accreditation bodies thot verv |mportant position especially in maintainins the suolin of wfr institutions. Thirdly, ?rffi fistitutions In sevZral-ciitiet itii"a, received evaluation whereas. Their national accreditation 6oaii, did Not evatuate tty_g"rs in soii "oiiii.-’ri,iiinii’in, accreditation in the Wet institutions generitty ieri ii’-l*ift getting: communifit" support, acceDtonce in prolesonor organimtio4 receiing especially for federal fuads, acduirins non ,w,ff’,i;#ii;f i[!trlw:,i*,xpx;;"ytrf , ’t![#f ili, iı,Wffi pr?grqm gwde if i,;:,;i"ffi!";["f ;:!t:i:;; -tines; enlyqcing linkage betwden vocational scnoo anct tndustry; including new pblicy regardint imole_ y:T!!!?" of accrediianon:anfl iiprofiig-in; -frrji"W’f;,industry. , number=1, journal=Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, author=Sukardi, Sukardi, year=2018, month=Apr.